Production, Characterization, and In Vitro Antifungal Evaluation of Itraconazole-Loaded Fibrous Sheets Prepared by Electrospinning with a Factorial Design - Emőke-Margit Rédai; Orsolya Péterfi; Attila Levente Gergely; Enikő Barabás; Andrada Pintea; Paula Antonoaea; Robert-Alexandru Vlad; Nicoleta Todoran; Cornelia-Titiana Cotoi; Adriana Ciurba; Emese Sipos (Applied Sciences)
Itraconazole (ITZ) is a broad-spectrum triazole antifungal agent suitable for the treatment of superficial and systemic mycoses. This study aimed to formulate, characterize, and evaluate the in vitro antifungal performance of single-jet electrospun itraconazole-loaded polyvinylpyrrolidone-based fibers. Fibrous mats were prepared under the following experimental conditions: 10, 12.5, and 15 cm needle–collector distance, 20 kV tension, and 1, 1.5, and 2 mL/hour flow rate. The fibers were characterized by SEM, DSC, FTIR, assays, disintegration tests, dissolution tests, and in vitro antifungal activity. Using a 22 factorial design, the effects of preparation variables on the characteristics of the fibrous sheets were described. The electrospinning process led to smooth-surfaced, randomly oriented, and bead-free fibers. The average fiber diameter ranged from 887 nm to 1175 nm. The scanning calorimetry of pure ITZ revealed a sharp endothermic melting point at a temperature of 170 °C, not present in the curves of the fibers. After 60 min, between 70 and 100% of ITZ was released. The antifungal assay revealed that the fibers inhibited the growth of Candida albicans and Candida parapyilosis. The obtained fiber mats prepared from the hydrophilic polymer presented almost instantaneous disintegration, with potential applications for rapid antifungal delivery in oral or topical pharmaceutical form.